2018
DOI: 10.1007/s12630-018-1178-z
|View full text |Cite
|
Sign up to set email alerts
|

Awake craniotomy using dexmedetomidine and scalp blocks: a retrospective cohort study

Abstract: Dexmedetomidine-based anesthesia and scalp block facilitated AC surgery without any requirement for urgent airway intervention or unplanned conversion to a full general anesthetic. This approach can enable physiologic testing before and during tumour resection facilitating real-time surgical decision-making based on intraoperative brain mapping with patients awake thereby minimizing the risk of neurologic deficit and increasing the opportunity for optimal surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
(45 reference statements)
1
24
0
3
Order By: Relevance
“…This secondary outcome has informed our use of scalp block for awake craniotomy procedures where we find a circumferential scalp block to be an important aspect of the anesthetic management for patients undergoing awake craniotomy. 5,6 Notably, we did not find any significant differences in the long-term secondary outcomes at postoperative day 30 or 60, and see no reason to believe that the effect at 90 days would be any different.…”
Section: To the Editormentioning
confidence: 51%
“…This secondary outcome has informed our use of scalp block for awake craniotomy procedures where we find a circumferential scalp block to be an important aspect of the anesthetic management for patients undergoing awake craniotomy. 5,6 Notably, we did not find any significant differences in the long-term secondary outcomes at postoperative day 30 or 60, and see no reason to believe that the effect at 90 days would be any different.…”
Section: To the Editormentioning
confidence: 51%
“…18 In addition to patient factors, a small number of studies have investigated whether the surgical approach itself has any effect, i.e., specifically if scalp blocks and dexmedetomidine are associated with ISs in patients undergoing awake craniotomy, but did not find this to be a significant contributor. 19,20 As evidenced from the variety of variables that have been found across centers, it is difficult to appreciate a reproducible risk factor that would aid in predicting IS. To date, no papers have been published discussing predictors of ADs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study comparing propofol-remifentanil and dexmedetomidine during awake craniotomy in patients undergoing supratentorial tumor resection, dexmedetomidine provided comparable surgical environment in terms of quality of intraoperative brain mapping and efficacy of sedation, with less respiratory adverse events compared with the propofol-remifentanil group [ 24 ]. Similarly, a retrospective cohort study including 55 patients demonstrated that dexmedetomidine and the scalp nerve block were used successfully in awake craniotomy without any urgent airway intervention or unplanned conversion to general anesthesia [ 25 ]. Although high dose of dexmedetomidine may cause bradycardia, significant inter-individual variability of the sedative state, and a prolonged recovery from sedation after the cessation of infusion, such a high dose is not required during awake craniotomy.…”
Section: Anesthetic Approaches For Awake Craniotomy: Sedative Componementioning
confidence: 99%